Effectiveness of Educational Game Method in Improving The Concept of Mathematical Operations - Laylatul Hisda; Lalu Gede Damar Wulan; Ivan Luthfi Ihwani; Andika Ellena Saufika Hakim Maharani (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
The low emphasis on mathematical operation concepts in elementary school students is a problem that is often encountered. The educational game method in learning can improve the idea of mathematical operations. The quantitative study was conducted by collecting Pretest-Posttest answers in offline worksheets in the classroom. The research subjects were 5th-grade students of SD Negeri 4 Mataram. We analyzed the data by paired sample t-test to see whether the initial hypothesis was accepted or rejected. Based on the results, it is observed that the use of educational game methods can significantly improve the concept of mathematical operations for 5th-grade students. The obtained grades increase from a minimum of 25% to a maximum of 100%, with an average increase of 57.22%. Based on these findings the researcher provides the following recommendations: (1) Teachers should present variations of math learning so that students are not bored and interested during the learning process (2) Schools should support learning by providing the necessary learning materials so that learning objectives can be achieved. (3) Researchers should study methods other than educational game methods so that they can provide recommendations to teachers regarding effective learning methods to be applied in learning.